Teaching in Hospitals and Healthcare Resorts: A Qualitative Study of Teachers' Needs - Agnieszka Małkowska-Szkutnik; Aleksandra Berkowska; Maja Gajda; Dorota Kleszczewska (MDPI AG, 2021)
The daily functioning of children who suffer from chronic conditions may be limited by the disease and by hospitalization. Hospital schools have an important role in counterbalancing those negative effects. The aim of the study was to define hospital schools' teachers' needs. The data from qualitative research conducted on 21 Polish hospital school teachers was included in the analysis. A semi-structured interview method was chosen. Researchers played an active role as moderators. Thirty-four descriptive codes were assigned to the main five areas of needs related to: work conditions, the character of work, psychological support, self-fulfillment, and social relations. The results showed that the teachers were concerned about hospital school marginalization, they received no mental health support, and felt that the extent of their role was underestimated by medical staff. The lack of recognition is likely to make teachers feel frustrated, and demotivated. By learning more about what hospital teachers think of their work, it is possible to create recommendations for changes. There seems to be a need to raise awareness of the importance of schools in health care institutions.